2019
DOI: 10.1039/c8md00527c
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, andin vitroandin vivocharacterization of 1-{4-[4-(substituted)piperazin-1-yl]butyl}guanidines and their piperidine analogues as histamine H3receptor antagonists

Abstract: The prominent members of 1-{4-[4-(substituted)piperazin-1-yl]butyl}guanidines as histamine H3 receptor antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This observation is consistent with the results of previous experiments. 31 We found that the activity differences in the studied group of compounds are related to ligand alignment in the hydrophobic regions between TM2, TM3, and TM7. This area includes a number of aromatic amino acids such as Y91 2.61 , Y94 2.64 , W110 3.28 , F398 7.39 , and W402 7.43 .…”
Section: Table 2 Radioligand Binding Results At Humanmentioning
confidence: 77%
See 4 more Smart Citations
“…This observation is consistent with the results of previous experiments. 31 We found that the activity differences in the studied group of compounds are related to ligand alignment in the hydrophobic regions between TM2, TM3, and TM7. This area includes a number of aromatic amino acids such as Y91 2.61 , Y94 2.64 , W110 3.28 , F398 7.39 , and W402 7.43 .…”
Section: Table 2 Radioligand Binding Results At Humanmentioning
confidence: 77%
“…Compounds based on 1-[4-(piperazin-1-yl)but-1-yl]guanidine proved to be key to maintaining a high affinity at the histamine H 3 R. Based on previously obtained data of the guanidine series, two representative of the lead compounds, that is, ADS1017 and ADS1020 , were selected for further structural optimization. 31 , 32 In this paper, we have focused on the synthesis and pharmacological evaluation of a guanidine series where a flexible alkyl chain consisting of seven methylene groups, present in the lead compounds, is replaced by 1,4-cyclohexylene or p -phenylene group connected directly or by a methylene group to piperazine and phenoxy moieties. Additionally, for derivatives bearing a 1,4-disubstituted cyclohexylene group, the ( E ) and ( Z ) isomers were separated and pharmacologically tested independently ( Chart 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations